Pharmacogenomic Testing to Guide Personalized Cancer Medicine Decisions in Private Oncology Practice: A Case Study - Astras, George; Papagiannopoulos, Christos I.; Kyritsis, Konstantinos A.; Markitani, Constantina; Vizirianakis, Ioannis S. (Frontiers in Oncology, 2020)
Innovative tumor profiling methodologies are utilized to elucidate the pharmacogenomic landscape of tumor cells in order to support the molecularly-guided delivery of therapeutics. Indeed, improved clinical outcomes are achieved in oncology practice by providing the physicians with expert-guided, standardized and easily interpretable knowledge, translated from molecular profiling analysis to support clinical decision-making. However, there is still limited utilization of the technology especially in small private oncology practices. In this work, we analyzed how molecularly-guided interventions in seventeen consented cancer patients led to an overall improvement of disease response rates in a private oncology center. The precision medicine strategy was based on the OncoDEEP™ profiling solutions, and focused on finding clinically-actionable relationships between tumor biomarkers and drug responses. The obtained data support the notion that: a) following the pharmacogenomic derived recommendations favorably impacted cancer therapy progression; and b) the earlier profiling followed by the delivery of molecularly-targeted therapy led to more durable and improved pharmacological response rates. Moreover, we report the example of a patient with metastatic gastric adenocarcinoma who, based on the molecular profiling data, received an off-label therapy which resulted in a complete response and a current cancer-free maintenance status. Overall, our data provide a paradigm on how molecular tumor profiling can improve decision making in the routine private oncology practice.